Design and analysis of radiaxial induction motor - AKÜNER, MUSTAFA CANER; DEMİR, UĞUR (SPRINGER, 2018)
In this study, design and analysis studies of an asynchronous motor with a tapered geometry for a two-person electric vehicle were carried out. The goal of this study is to analyze change in the taper angle for this asynchronous motor in terms of the power factor, efficiency, starting torque, breakdown torque, and rated torque. First, the vehicle dynamics and the asynchronous motor structure were analyzed. Then, axial, radial, and hybrid (radiaxial) flux electric motor models and the purpose of these models were investigated. Literature studies have shown that there is no work related to angle optimization for a radiaxial flux with a conical geometry hybrid structure for an asynchronous motor. The required motor characteristics for a two-person electric vehicle have been calculated. Then, the package volume for the in-wheel motor was analyzed, and the maximum diameter and length of the asynchronous motor were determined. The minimum diameter of this engine package was also specified considering magnetic limit conditions such as saturation factor for rotor and stator of the asynchronous motor. Nine asynchronous motor models were designed and analyzed considering the maximum and minimum motor diameters to investigate the optimal taper angle of this asynchronous motor. And the results were discussed and evaluated.
Keywords: Electric vehicles; Finite element analysis; Induction motor; Magnetic flux; Traction motors